1982
DOI: 10.1056/nejm198208193070802
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Coliform Infection in Acutely Dysuric Women

Abstract: We reevaluated conventional criteria for diagnosing coliform infection of the lower urinary tract in symptomatic women by obtaining cultures of the urethra, vagina, midstream urine, and bladder urine. The traditional diagnostic criterion, greater than or equal to 10(5) bacteria per milliliter of midstream urine, identified only 51 per cent of women whose bladder urine contained coliformis. We found the best diagnostic criterion to be greater than or equal to 10(2) bacteria per milliliter (sensitivity, 0.95; sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
307
0
9

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 679 publications
(323 citation statements)
references
References 15 publications
7
307
0
9
Order By: Relevance
“…This study confirmed that the prevalence of UTI among female diabetics was higher when compared to prevalence in males (6).Bacteriological study reveals the involvement of gram -ve enteric organisms that commonly cause UTI such as E coli , Klebsiella species and Proteus species [9,[19][20][21][22][23][24][25].…”
Section: Discussion:-supporting
confidence: 64%
“…This study confirmed that the prevalence of UTI among female diabetics was higher when compared to prevalence in males (6).Bacteriological study reveals the involvement of gram -ve enteric organisms that commonly cause UTI such as E coli , Klebsiella species and Proteus species [9,[19][20][21][22][23][24][25].…”
Section: Discussion:-supporting
confidence: 64%
“…Its high sensitivity in the order of 0.2 lW allows detection of 10 2 active microorganisms per sample. This is even more important as studies comparing voided urine specimens and bladder aspirate specimens in women with UTI have shown that the traditional criterion for a positive culture of voided urine (10 5 CFU/mL) is insensitive for cystitis, and 30-50 % of women with bladder infection have colony counts of 10 2 -10 4 CFU/mL in voided urine [18], a range that is mostly covered by IMC. In our present study conditions (i.e., artificial urine), the high sensitivity of isothermal microcalorimetry (IMC) allowed the rapid detection of all urinary tract pathogens (UTP) investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This finding adds to the ongoing discussion about the most appropriate cutoff value. 5,6 Strengths and limitations To our knowledge, this is the first study investigating the correlation between the severity of symptoms or bacteriuria and the duration of symptoms. The design of the diary was based on previous qualitative and cross-sectional research to maximize its validity.…”
Section: Duration Of Symptomsmentioning
confidence: 99%
“…Furthermore, although a bacterial culture of > 100,000 colony-forming units (CFU)/mL is generally accepted as defining an infection of the urinary tract, many authors describe the same symptoms in patients with lower levels of bacteriuria and even in culture-negative women. [4][5][6][7] It has even been suggested that antibiotic therapy was effective in culture-negative women. 8 These conflicting observations demonstrate that much is unclear about the clinical evolution of signs and symptoms in women with suspected cystitis who are receiving antimicrobial treatment.…”
mentioning
confidence: 99%